Low Coordination State RhI‐Complex as High Performance Catalyst for Asymmetric Intramolecular Cyclopropanation: Construction of penta‐Substituted Cyclopropanes. Issue 10 (24th January 2023) - Zhang, Junyou; Xu, Weici; Xu, Ming‐Hua
Abstract: A simple, broad‐scope rhodium(I)/chiral diene catalytic system for challenging asymmetric intramolecular cyclopropanation of various tri ‐substituted allylic diazoacetates was successfully developed. The low coordination state Rh I ‐complex exhibits an extraordinarily high degree of tolerance to the variation in the extent of substitution of the allyl double bond, thus allowing the efficient construction of a wide range of penta ‐substituted, fused‐ring cyclopropanes bearing three contiguous stereogenic centers, including two quaternary carbon stereocenters, in a highly enantioselective manner with ease at catalyst loading as low as 0.1 mol %. The stereoinduction mode of this Rh I ‐carbene‐directed asymmetric intramolecular cyclopropanation was investigated by DFT calculations, indicating that π‐π stacking interactions between the aromatic rings of chiral diene ligand and diazo substrate play a key role in the control of the reaction enantioselectivity. Abstract : A simple, broad‐scope rhodium (I)/chiral diene catalytic system has been developed that allows otherwise difficult‐to‐access penta ‐substituted cyclopropanes to be prepared in a highly enantioselective manner through asymmetric intramolecular cyclopropanation of rather challenging tri ‐substituted allylic diazoacetates. Extraordinary high performance of Rh I /diene complex is showcased with low catalyst loading as little as 0.1 mol %.